Comparative Study Between the Compilation of Islamic Law and the Four Schools of Thought on the Concept of Reconciliation - Ahmad Hafidz Safrudin; Erik Afriyuda (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Agama Islam YAPTIP Chadijah Ismail Pasaman Barat, 2025)
In Islam, the concept of rujuk or return after divorce (especially divorce raj'i) is a form of Allah's compassion for His servants, so that divorced couples still have the opportunity to repair the relationship, as long as it is still in the iddah period (waiting period after divorce). Reconciliation can be a means of mutual reflection and evaluation so that previous conflicts are not repeated. Reconciliation is not just a formality, but requires sincere intention from both parties to improve the relationship, awareness of previous mistakes, healthy communication and guidance (for example through family counseling or clerical advice). However in Islam that Islam strongly encourages reconciliation if it brings maslahah (good) to both parties and the family, especially the children, but also makes room if separation is the best course. Scholars agree that reconciliation is allowed in Islam. This rujuk effort is the last alternative to reconnect the physical and mental relationship between husband and wife that was cut off due to divorce (thalak raj'i). Based on the analysis that the author has done, there are differences of opinion among the four madhhabs. Of the four opinions, Imam ash-Shafi'i's opinion is considered the most relevant in the Indonesian context, because the Islamic legal system in Indonesia generally refers to the Shafi'i Mazhab which emphasizes the clarity of speech and the importance of the presence of witnesses in the reconciliation process.